Reframing the Debate Between Agency and Stakeholder Theories of the Firm - Shankman, Neil A. (Journal of business ethics, 1999)
The conflict between agency and stakeholder theories of the firm has long been entrenched in organizational and management literature. At the core of this debate are two competing views of the firm in which assumptions and process contrast each other so sharply that agency and stakeholder views of the firm are often described as polar opposites. The purpose of this paper is to show how agency theory can be subsumed within a general stakeholder model of the firm. By analytically deconstructing the assumptions of agency theory, it is argued that agency theory: (1) must include a recognition of stakeholders; (2) requires a moral minimum to be upheld, which places four moral principles above the interests of any stakeholders, including shareholders; (3) consists of contradictory assumptions about human nature and which give rise to the equally valid assumptions of trust, honesty and loyalty to be infused into the agency relationship. In this way, stakeholder theory is argued to be the logical conclusion of agency theory. Empirical hypotheses are presented as a means to substantiate this claim.